2017
DOI: 10.1016/j.tws.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness degradation of composite skin fields due to strength and buckling onset

Abstract: Suitable and fast calculation methods with sufficient accuracy are required to optimise large composite structures. The present paper introduces a progressive stiffness degradation analysis (PSDA), which computes skin buckling onset and strength failure initiation of skin fields separated by stiffeners, as well as the subsequent damage propagation using closed form solutions. This constitutes a simplified, but much faster approach compared to state of the art progressive failure analyses, which incorporate fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The design variables in the optimization process are ply thickness and fiber angle orientation. Primarily, the laminates consist of nine layers, as per Führer [42]. Concerning the choice of optimization technique, Cakiroglu et al [23] have shown that the harmony search (HS) optimization technique was capable of obtaining dispersed stacking sequences that perform better than conventional sequences, such as the [45, −45, 0, 90, 0, 90, 0, −45, 45] fiber angle sequence used by Führer [42].…”
Section: Scope and Objectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…The design variables in the optimization process are ply thickness and fiber angle orientation. Primarily, the laminates consist of nine layers, as per Führer [42]. Concerning the choice of optimization technique, Cakiroglu et al [23] have shown that the harmony search (HS) optimization technique was capable of obtaining dispersed stacking sequences that perform better than conventional sequences, such as the [45, −45, 0, 90, 0, 90, 0, −45, 45] fiber angle sequence used by Führer [42].…”
Section: Scope and Objectivesmentioning
confidence: 99%
“…Primarily, the laminates consist of nine layers, as per Führer [42]. Concerning the choice of optimization technique, Cakiroglu et al [23] have shown that the harmony search (HS) optimization technique was capable of obtaining dispersed stacking sequences that perform better than conventional sequences, such as the [45, −45, 0, 90, 0, 90, 0, −45, 45] fiber angle sequence used by Führer [42]. The present study adopted the optimum stacking sequence from the analyses done by Cakiroglu et al [23] as a starting configuration and further improved this stacking sequence in the presence of cut-outs.…”
Section: Scope and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations